Studies towards the synthesis of novel, coumarin-based HIV-1 protease inhibitors - Rashamuse, Thompho Jason (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
A series of the Baylis-Hillman adducts have been obtained by reacting protected O-benzylated and unprotected substituted salicylaldehydes with methyl acrylate or tertbutyl acrylate, respectively, using DABCO as catalyst. Treatment of the Baylis-Hillman adducts with HCl in a mixture of acetic acid and acetic anhydride afforded the corresponding 3-(chloromethyl)coumarin derivatives with yields of up to 94%. Similar use of HI afforded the corresponding 3-(iodomethyl)coumarins but, depending on the reaction time, the reduced 3-methyl analogues could also be obtained. Arbuzov reactions of the 3-(halomethyl)coumarin derivatives have been undertaken to afford 4-phosphorylated and 1'-phosphorylated derivatives, regioselectivity being dependent on the halide-leaving group. The 3-(chloromethyl)coumarin derivatives have been subjected to nucleophilic (SN) attack by benzylamine to give the corresponding 3- [(benzylamino)methyl]coumarin derivatives in yields of up to 74%. Further treatment of the 3-[(benzylamino)methyl]coumarin derivatives with chloroacetyl chloride afforded the chloroacetamide derivatives, which exhibit hindered rotation about the amine C(O)-N bond. The acetamide derivatives have also been subjected to Arbuzov reaction conditions to afford the phosphorylated derivatives in yields of up to 86%. In a preliminary modelling study, hydrolysed analogues of the synthesized phosphorylated derivatives have been docked into the active site of the HIV-1 protease enzyme using the Cerius-2 Ligandfit software module to provide an insight into potential receptor-ligand hydrogen bonding interactions.
Keywords: Coumarins; Protease Inhibitors; HIV infections -- Treatment; HIV (Viruses); AIDS (Disease) -- Treatment; Heterocyclic compounds -- Derivatives